The Indonesian-English Code-Switching Used by Najwa Shihab and Agnes Mo on Catatan Najwa YouTube Channel - Nita Ayu Cahyani; I Made Iwan Indrawan Jendra; Komang Sulatra (ID Solutions, 2021)
Code-Switching is one of the phenomenon of language in society where the people use more than one language alternately in their utterances. It can occur spontaneously but some people may do it on purpose. This study was focused on analyzing the functions of Indonesian-English Code-Switching as found in Najwa Shihab and Agnes Mo conversation on Catatan Najwa Youtube Channel. The data source in this research was taken from one of the videos entitled “Najwa Shihab X Agnes Mo”. For the analysis, the researcher used the theory proposed by Gumperz (1982) to identify the functions of the code-switching. In collecting the data, this study used direct observation method and descriptive qualitative method was applied in analysing the data. The data that had been analysed were presented by using simple table and picture as well as descriptively. The result found that from the six functions of code-switching, only five were found, namely: Quotation (7 data) Interjection (23 data), Reiteration (27 data), Message Qualification (25 data), and Personalization vs. Objectification (3 data). The function that was not found is Addressee Specification.